Reasons for Composite Restoration Replacement in an Iranian Population - Nouroozi Loraki, Kowsar; Ghanatir, Elham (Galen Medical Journal, 2024)
Background: This study aimed to assess the reasons for composite restoration replacement in patients in Ahwaz, Iran. Materials and Methods: This cross-sectional study was conducted on 231 patients presenting to the dental clinic of the School of Dentistry, Ahwaz Jundishapour University in 2017-2018 who required composite restoration replacement. A senior dental student performed a clinical dental examination of patients using a dental explorer, a dental mirror, and dental floss, and the decayed, missed, and filled (DMF) index of the patients was recorded. The patients also underwent radiography. The reason for composite restoration replacement was recorded. Data were analyzed by independent t-test, Chi-square test, one-way ANOVA, and LSD test (alpha=0.05). Results: Of 231 patients, 104 (45%) were males and 127 (55%) were females. The majority of the patients (27.3%) were between 40-50 years and had Class II malocclusion (62%). The mean DMF of patients was 3.48±1.36. Maxillary anterior teeth comprised the majority of the teeth that required restoration replacement. Secondary caries was the most common cause of restoration replacement (23.4%), followed by a combination of secondary caries and pain or dentin hypersensitivity (15.1%). The reason for restoration replacement had a significant association with age with primary caries being most prevalent in the 41-50 age group (P<0.05) but had no significant association with gender or class of occlusion (P>0.05). Patients requiring restoration replacement due to primary and secondary caries, and broken or cracked restorations had significantly higher mean DMF values compared to those with other reasons (P=0.031). Conclusion: Secondary caries was the most common reason for composite restoration replacement in the study population, and the reason for restoration replacement had a significant association with age and DMF of patients.